STRATEGI DAN MODEL PEMBELAJARAN SENI RUPA BAGI ANAK BERKEBUTUHAN KHUSUS - Lia Mareza (Psychopolytan : Jurnal Psikologi, 2018)
Learning models and strategies based on a uniform curriculum can improve efficiency but decrease the effectiveness of achieving the learning objectives themselves. Learning based on individual student needs will be more effective although it can not be done by teachers on a large class scale. Children with special needs can participate fully in school life and be able to receive teaching or curriculum relevant to their needs. Taking into account the existence of special needs children, educators or teachers should have more material, model, and strategy to meet the needs of all children with special needs in the educational environment. The sooner or earlier in identifying the child with special educational needs, the easier it will be for the teacher to meet the individual needs, so that the strategy approach or the learning model can be applied as education for the children with special needs. The problems studied are: a) How is the art learning strategy for children with special needs? b) How is the preparation of art learning media for children with special needs? c) What learning model is developed so that children with special needs can work fine art well? Type of research method used in this research is qualitative method. Qualitative methods are observation, interview, or document review. The results show that the inclusion learning process is in grades 3 and 5 of Inclusive School by combining regular classes and special needs children. Supporting factors of learning process are adequate facilities and infrastructures, support from Directorate of Special Education, teachers make special program for learning process but inhibiting factor that is, lack of parent role in progress process ability of children with special needs, teacher and class assistant which does not come from special education and art, the teacher does not make the classroom administration, the teacher is less innovative in delivering art lesson material and the lack of special needs children in this inclusion school because the special students have fulfilled the percentage of sharing with the regular class.